Plasma exosomes in OSA patients promote endothelial senescence: effect of long-term adherent continuous positive airway pressure. Issue 2 (25th September 2019) - Khalyfa, Abdelnaby; Marin, Jose M; Qiao, Zhuanhong; Rubio, David Sanz; Kheirandish-Gozal, Leila; Gozal, David
Abstract: Obstructive sleep apnea (OSA) is associated with increased risk for end-organ morbidities, which can collectively be viewed as accelerated aging. Vascular senescence is an important contributor to end-organ dysfunction. Exosomes are released ubiquitously into the circulation, and transfer their cargo to target cells facilitating physiological and pathological processes. Plasma exosomes from 15 patients with polysomnographically diagnosed OSA at baseline (OSA-T1) after 12 months of adherent continuous positive airway pressure (CPAP) treatment (OSA-T2), 13 untreated OSA patients at 12-month intervals (OSA-NT1, OSA-NT2), and 12 controls (CO1 and CO2) were applied on naïve human microvascular endothelialcells-dermal (HMVEC-d). Expression of several senescence gene markers including p16 ( CDKN2A ), SIRT1, and SIRT6 and immunostaining for β-galactosidase activity (x-gal) were performed. Endothelial cells were also exposed to intermittent hypoxia (IH) or normoxia (RA) or treated with hydrogen peroxide (H2 O2 ), stained with x-gal and subjected to qRT-PCR. Exosomes from OSA-T1, OSA-NT1, and OSA-NT2 induced significant increases in x-gal staining compared to OSA-T2, CO1, and CO2 ( p -value < 0.01). p16 expression was significantly increased ( p < 0.01), while SIRT1 and SIRT6 expression levels were decreased ( p < 0.02 and p < 0.009). Endothelial cells exposed to IH or to H2 O2 showed significant increases in x-gal staining ( p < 0.001) and in senescence gene expression. Circulating exosomes in untreated OSA induce marked and significant increases in senescence of naïve endothelial cells, which are only partially reversible upon long-term adherent CPAP treatment. Furthermore, endothelial cells exposed to IH or H2 O2 also elicit similar responses. Thus, OSA either directly or indirectly via exosomes may initiate and exacerbate cellular aging, possibly via oxidative stress-related pathways.